Retinal and optic nerve degeneration in α-mannosidosis - Juliane Matlach; Thea Zindel; Yasmina Amraoui; Laila Arash-Kaps; Julia B. Hennermann; Susanne Pitz (Orphanet Journal of Rare Diseases, 2018)
Abstract Background α-mannosidosis is a rare, autosomal-recessive, lysosomal storage disease caused by a deficient activity of α-mannosidase. Typical symptoms include intellectual, motor and hearing impairment, facial coarsening, and musculoskeletal abnormalities. Ocular pathologies reported previously were mainly opacities of the cornea and lens, strabismus, and ocular motility disorders. However, retinal and optic nerve degeneration have been rarely described. Methods We report ocular findings of 32 patients with α-mannosidosis. We particularly concentrated on retinal abnormalities which we supported by posterior segment examination, fundus photography, and Spectral-Domain optical coherence tomography (SD-OCT) imaging. Results Tapeto-retinal degeneration with bone spicule formations in the peripheral retina or macular changes were seen in three patients (9.4%) on funduscopy; of these, two with optic nerve atrophy. Eight retinal images could be obtained by OCT or fundus photography; of these, six showed thinning of the outer retinal layers on OCT. Overall, optic nerve atrophy was seen in six patients (18.8%); of these, four with partial atrophy. Two patients had partial optic nerve atrophy with no retinal abnormalities on funduscopy. Cataract was seen in two (6.3%), corneal haze also in two patients (6.3%). Six patients (18.8%) had manifest strabismus, four (12.5%) nystagmus, and in five patients (15.6%) impaired smooth pursuit eye movements were seen. Conclusion Ocular pathologies are not exclusively confined to opacities of the cornea and lens or strabismus and ocular motility disorders but tapeto-retinal degeneration and optic nerve atrophy may be a common feature in α-mannosidosis. OCT technology helps detecting early outer retinal thinning which can progress with age and potentially leads to vision loss over time.